Design of a low-power optical front-end receiver for wireless communication applications - Lim, Sharon Xueqi. (2011)
Wireless optical communication (WOPCOM) is a high-speed, high-capacity technology that uses white LED light to transmit information through free space. WOPCOM technology operates a little differently from existing optical and wireless networks. Data is converted into optical light and transmitted via white LEDs instead of laser or infrared radiation. This allowed the LEDs to provide illumination while simultaneously enabling information to be exchanged freely between devices and services without the hassles of cables. A WOPCOM device contains a WOPCOM transceiver which is able to provide communication, interconnection, signal processing, data exchange and control functions for devices such as audio player, laptops and desktop PCs through very-high-speed optical wireless data-links. It can also be used for communication among devices that have sufficient access to optical light. WOPCOM works best in an indoor environment.